2015
DOI: 10.4236/as.2015.62027
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Carbon Dioxide and Soil Moisture on Early Growth Response of Soybean

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 95 publications
1
2
0
1
Order By: Relevance
“…This suggests that e[CO2] inhibits the positive effect of high light intensity on leaf production. In line with our results, a 23% reduction in the number of leaves have been reported in soybean; however, the effect of e[CO2] on the number of leaves depended on the plant growth stage (Madhu & Hatfield 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that e[CO2] inhibits the positive effect of high light intensity on leaf production. In line with our results, a 23% reduction in the number of leaves have been reported in soybean; however, the effect of e[CO2] on the number of leaves depended on the plant growth stage (Madhu & Hatfield 2015).…”
Section: Discussionsupporting
confidence: 92%
“…However, there are divergent reports on the effect of elevated CO2 concentration (e[CO2]) on different plant species (Croonenborghs et al 2009). It was found that environmental factors, including nitrogen (Robinson et al 2012) and other elements (De Graaff et al 2006;Lotfiomran et al 2016), temperature (Lee 2011;Madan et al 2012;Kumari et al 2019), water availability (Madhu & Hatfield 2015), ____________________________________________________________________________________________________________________ air pollutants (Volin & Reich 1996), drought (Miranda-Apodaca et al 2018), and light (Kerstiens 2001;Pérez-López et al 2015) determine the magnitude of plant response to e[CO2]. Naing et al (2016) suggested an interaction between supplemental lighting and e[CO2] of the rose, and reported that the greatest increase in growth rate was achieved when e[CO2] was applied together with additional lightning (Naing et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Root growth of most of the crops is enhanced under elevated atmospheric CO 2 (Rogers et al, 1994;Pritchard and Amthor, 2005), often to a greater extent than leaves, stem, and reproductive structures (Norby et al, 2001 andKimball et al, 2002). According to Madhu and Jerry (2015), high CO 2 might have inhibited the growth at early stage of crop but due to adoptive mechanism to high CO 2 plants were recovered and responded physiologically at later stage. This is in accordance with Dogridge cuttings under eCO 2 at 50 DAP.…”
Section: Root Numbermentioning
confidence: 99%
“…Kondisi lingkungan seperti intensitas cahaya, kelembapan udara, dan suhu merupakan faktor pembatas bagi pertumbuhan dan perkembangan tanaman kacang khususnya untuk karakteristik morfologi dan fisiologinya (Broughton 2003). Madhu & Hatfield (2015) menyatakan bahwa intensitas cahaya yang tinggi dapat merangsang pembukaan stomata dan meningkatkan konsentrasi CO 2 interseluler di daun sehingga dapat meningkatkan laju fotosintesis. Namun, jika intensitas cahaya matahari melebihi batas optimal maka mengakibatkan kelembapan udara rendah, dan transpirasi tinggi sehingga dapat menurunkan laju fotosintesis.…”
unclassified